Description of the newly-hatched juvenile of Aegla paulensis (Decapoda, Anomura, Aeglidae) - de Moraes, Juliana Cristina Bertacini; Bueno, Sérgio Luiz De Siqueira (Zootaxa, 2013)
The postembryonic development of Aegla paulensis is epimorphic (= direct), in which the hatching form is a juvenile that morphologically resembles the adult. Hatching is asynchronous, taking 3–5 days for all juveniles from a single brood to hatch. This paper provides a complete description of the external morphology of the newly-hatched juvenile of A. paulen-sis as analyzed through light microscopy (LM) and scanning electron microscopy (SEM). One of the striking features ob-served in the newly-hatched juvenile of A. paulensis was the presence of four pairs of rudimentary pleopods, a trait never described before in early juveniles of Aegla. Additional novelties include three unique types of setae and two types of pore sensilla.